Patient-Reported Outcomes Improves the Prediction of In-patient and Emergency Department Readmission Risks in Coronary Artery Disease. (2018) - Southern, Danielle; Norris, Colleen; Quan, Hude; Santana, Maria; James, Matthew; Wilton, Stephen; Lawal, Oluwaseyi; Liang, Zhiyang; Awosoga, Oluwagbohunmi; Graham, Michelle; Ghali, William; Knudtson, Merril; et al.
No abstract available